2021
DOI: 10.1186/s13578-021-00581-w
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory roles and mechanisms of alternative RNA splicing in adipogenesis and human metabolic health

Abstract: Alternative splicing (AS) regulates gene expression patterns at the post-transcriptional level and generates a striking expansion of coding capacities of genomes and cellular protein diversity. RNA splicing could undergo modulation and close interaction with genetic and epigenetic machinery. Notably, during the adipogenesis processes of white, brown and beige adipocytes, AS tightly interplays with the differentiation gene program networks. Here, we integrate the available findings on specific splicing events a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 122 publications
(91 reference statements)
0
31
0
Order By: Relevance
“…Indeed, SE are more prone to creating and changing the protein function due to the deletion of functional motif [ 51 , 52 ]. Moreover, accumulating evidence has suggested that mutations and/or altered expression in splicing regulators and aberrant splicing alterations in the obesity-associated genes are often linked to humans’ diet-induced obesity and metabolic dysregulation phenotypes [ 53 ]. It is well known that choline was involved in regulating the host’s lipid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, SE are more prone to creating and changing the protein function due to the deletion of functional motif [ 51 , 52 ]. Moreover, accumulating evidence has suggested that mutations and/or altered expression in splicing regulators and aberrant splicing alterations in the obesity-associated genes are often linked to humans’ diet-induced obesity and metabolic dysregulation phenotypes [ 53 ]. It is well known that choline was involved in regulating the host’s lipid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, if PPARγ-1 activity is still poorly understood, PPARγ-2 has been demonstrated to be required for white adipogenesis [ 42 ]. This information is of great relevance since it indicates that mRNA splicing events are necessary to determine the fate of adipocyte precursor cells [ 43 , 44 ]. However, mRNA splicing is only one of many cellular processes that have recently been shown to be critical in the early stages of adipogenesis.…”
Section: Overview On Adipogenesismentioning
confidence: 99%
“…FTO is particularly interesting as it has the potential to regulate pre-mRNA splicing by altering the m 6 A pattern on pre-mRNAs as well as affecting the spliceosome via targeting m 6 A m and m 6 A in snRNAs [ 82 , 90 , 92 , 93 , 94 ]. Reduction of FTO leads to elevation of m 6 A, which promotes inclusion of dependent on SRSF2 (acting as an m 6 A reader) [ 95 ]. Similarly, to FTO, METTL16 revealed prevalently intronic binding in pre-mRNAs and its depletion led to an altered splicing pattern [ 96 ].…”
Section: A and M 6 A M Are Involved In Common Mechanisms Of Mrna Processing Stability And Translatimentioning
confidence: 99%